Three-dimensional volcano-acoustic source localization at Karymsky Volcano, Kamchatka, Russia - Rowell Colin R.; Fee David; Szuberla Curt A.L.; Arnoult Ken; Matoza Robin S.; Firstov Pavel P.; Kim Keehoon; Makhmudov Evgeniy (My University, 2014)
Abstract We test two methods of 3-D acoustic source localization on volcanic explosions and small-scale jetting events at Karymsky Volcano, Kamchatka, Russia. Recent infrasound studies have provided evidence that volcanic jets produce low-frequency aerodynamic sound (jet noise) similar to that from man-made jet engines. For man-made jet noise, noise sources localize along the turbulent jet flow downstream of the nozzle. Discrimination of jet noise sources along the axis of a volcanic jet requires high resolution in the vertical dimension, which is very difficult to achieve with typical volcano-acoustic network geometries. At Karymsky Volcano, an eroded edifice (Dvor Caldera) adjacent to the active cone provided a platform for the deployment of five infrasound sensors in July 2012 with intra-network relief of ~ 600 m. The network was designed to target large-scale jetting, but unfortunately only small-scale jetting and explosions were recorded during the 12-day experiment. A novel 3-D inverse localization method, srcLoc, is tested and compared against a more common grid-search semblance technique. Simulations using synthetic signals show that srcLoc is capable of determining vertical solutions to within ± 150 m or better (for signal-to-noise ratios ≥ 1) for this network configuration. However, srcLoc locations for explosions and small-scale jetting at Karymsky Volcano show a persistent overestimation of source elevation and underestimation of sound speed. The semblance method provides more realistic source locations, likely because it uses a fixed, realistic sound speed of ~ 340 m/s. Explosion waveforms exhibit amplitude relationships and waveform distortion strikingly similar to those theorized by modeling studies of wave diffraction around the crater rim. We suggest that the delay of acoustic signals and apparent elevated source locations are due to raypaths altered by topography and/or crater diffraction effects, implying that topography in the vent region must be accounted for when attempting 3-D volcano acoustic source localization. Though the data presented here are insufficient to resolve small-scale jet noise sources, similar techniques may be successfully applied to large volcanic jets in the future.
Keywords: Карымский; Kamchatka